2022
DOI: 10.1099/ijsem.0.005522
|View full text |Cite
|
Sign up to set email alerts
|

Micromonospora antibiotica sp. nov. and Micromonospora humidisoli sp. nov., two new actinobacterial species exhibiting antimicrobial potential

Abstract: Two novel actinobacterial strains, designated MMS20-R2-23T and MMS20-R2-29T, were isolated from riverside soil and subjected to taxonomic characterization. Both strains were Gram-stain-positive, aerobic, non-motile and filamentous, and formed orange to strong orange-brown coloured colonies, which later turned black. Both strains grew optimally at mesophilic temperatures, neutral to slightly alkaline pH and in the absence of NaCl. Analysis of 16S rRNA gene sequences indicated that the two novel strains fell int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In this study, we classified Micromonospora sp. AKA109, a producer of akazaoxime and A-76356, to M. humidisoli [ 40 ]. In contrast, Micromonospora sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we classified Micromonospora sp. AKA109, a producer of akazaoxime and A-76356, to M. humidisoli [ 40 ]. In contrast, Micromonospora sp.…”
Section: Discussionmentioning
confidence: 99%
“…M. humidisoli is very recently proposed, and its type strain, MMS20-R2-29 T , was isolated from riverside soil. It is explained that its growth occurs in the presence of 0–2% NaCl, with optimal growth at 0% NaCl [ 40 ]. In contrast, strain AKA109 was isolated from deep sea water with a higher salt concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, phenotypic comparison of Brevibacillus is not straightforward, as most strains show poor activities in biochemical and physiological tests [6,7]. Through a series of recent studies, riverside soil has been found to be a unique environment and also a rich source of microbial diversity [8][9][10]. In this study, a novel strain designated MMS20-4M-10-Y T was isolated from riverside soil.…”
Section: Introductionmentioning
confidence: 99%
“…Through a series of recent studies, riverside soil has been found to be a unique environment and also a rich source of microbial diversity [8–10]. In this study, a novel strain designated MMS20-4M-10-Y T was isolated from riverside soil.…”
Section: Introductionmentioning
confidence: 99%
“…Riverside soil environments harbour a great deal of prokaryotic diversity with various metabolic potential, from which we isolated and described a number of novel taxa in recent years [4][5][6][7][8][9][10]. In this study, a polyphasic taxonomic approach including phylogenetic, phenotypic and chemotaxonomic characterization was employed to describe two new species of Microcella isolated from riverside soil.…”
Section: Introductionmentioning
confidence: 99%